Case study of socio-legal conditionality of establishing a ban on criminal acts concerning land resources - Shulha, Andrii; Pavlykivskyi, Vitalii; Khramtsov, Oleksandr; Borysova, Larisa (Ecological Questions, 2020)
The problem of protecting land resources is currently relevant to the entire world community. On the basis of mathematical analysis of the dynamics indicators, it has been established that the number of criminal cases increased by 218 units (6.2%) during the last year compared with the previous year, while the number of closed criminal proceedings increased by 172 units (7.8%). The rate of growth shows an increasing trend both for the initiation (registration) of criminal proceedings in the land relations field, and for the termination of criminal proceedings due to the lack of corpus delicti. The forecast for the next three years showed that the load on the judicial system will increase every year, and the effectiveness of solving the problem of protecting land resources will remain extremely unsatisfactory. Therefore, it is necessary to improve legislation. The social conditionality factors of the criminal law prohibition are proposed, which together provide a sufficient basis for the necessity of recognizing socially dangerous offenses against land resources as criminally punishable. The criminal legislation analysis of foreign countries shows that only in Ukraine the regulatory framework provides the most complete protection of land resources. This positive experience can be used to create an optimal mechanism of criminal law protection of land resources at the international level.